Markers of emotional burnout experience in teachers - Tsukhai, Katsiaryna I. (Journal of the Belarusian State University. Philosophy and Psychology, 2026)
The author examines the essence of emotional burnout based on the attitude of a specialist to the activity performed. Through the phenomenological method of analysing transcripts of thematic interviews of teachers and subsequent content analysis of the results, markers are identified that reliably indicate the emotional burnout experience. It was found that when verbalising professional experience, respondents with varying degrees of emotional burnout mostly refer to the same categories. During the analysis, the identified categories are correlated with the components of K. Maslak’s three-dimensional burnout model. It is indicated that the results obtained can supplement the existing tools of practicing psychologists in the diagnosing emotional burnout and working with this condition.